2014
DOI: 10.1177/0969733014534876
|View full text |Cite
|
Sign up to set email alerts
|

Ethical considerations on the value of patient knowledge in long-term care

Abstract: This study deepens our understanding of the value of patient knowledge in situations where patients see the world in a different manner as do healthcare professionals. The conversations revealed personal subjective knowledge which our respondents create and live by. Healthcare professionals are encouraged to discover and affirm the understandings of these patients, and not be prepossessed due to the diagnosis or general nursing home rules. Understanding patients' unique knowledge through appreciation of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…I agree with Rensen et al (2018) on that the introduction of errorless skill learning in long-term Korsakoff care can result in massive reductions of behavioral problems (i.e. aggression and apathy), increased quality of life, and increased autonomy.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…I agree with Rensen et al (2018) on that the introduction of errorless skill learning in long-term Korsakoff care can result in massive reductions of behavioral problems (i.e. aggression and apathy), increased quality of life, and increased autonomy.…”
mentioning
confidence: 57%
“…One of the essential interventions used by Rensen et al (2018) was to ask the patients what skill they wanted to learn, hereby giving full support to the goals and values of the Korsakoff's syndrome patients themselves. The best results regarding learning, quality of life, and behavioral symptom reduction were seen in patients were the actual goals of the patient were accomplished.…”
mentioning
confidence: 99%
“…He can refer the patient to appropriate care services if necessary. However, GP's do not always recognise the disorder because it is a rare disorder, and Korsakoff patients are not aware of their illness and consequently do not have any care demands (van den Hooff & Goossensen, 2015b). This complicates the GP's ability to make a timely and proper diagnosis and to consult the existing guidelines (Federatie Medisch Specialisten, 2022; Galvin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that these patients have been given insufficient patient education or alternatively such that does not help to preserve the required knowledge. In addition, studies have demonstrated that lack of knowledge may increase the chance of adverse effects related to ineffective drug treatment 22,23 . On the other hand, high level of knowledge has a positive influence on patients' satisfaction 19 …”
Section: Introductionmentioning
confidence: 99%